Gene Vaccines - Thalhamer, Josef; Weiss, Richard; Scheiblhofer, Sandra; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2012)
The induction of antigen-specific immune responses after in vivo transfection with expression plasmids has triggered a revolution of vaccine research. After a first hype, evoked by the fascinating options of this method, clinical studies did not reach the ambitious aims and a phase of disillusion ensued. It became obvious that Gene vaccines displayed a weaker immunogenicity in humans than had been observed in the mouse models. Meanwhile these hurdles have been overcome and gene vaccines undergo a renaissance. The present book gives an update of the “world of naked gene vaccines”, namely DNA and RNA vaccines. Its content ranges from general mechanisms, inherent immunostimulatory properties and the vast potential to modulate immune responses, to recent successful clinical studies and approved veterinary gene vaccines. Beyond the state-of-the-art of genetic immunization, the reader will be stimulated with a chapter addressing “burning questions”.
Preface -- 1 General mechanisms of gene vaccines -- 2 Strategies to Improve DNA Vaccine Potency: HPV-associated Cervical Cancer as a Model System -- 3 Immune-activating mechanisms of replicase-based DNA and RNA vaccines and their role in immune-apoptosis -- 4 Cytokine genes as molecular adjuvants for DNA vaccines -- 5 Pharmaceutical non-viral formulations for gene vaccines -- 6 Rational design of formulated DNA vaccines: the DermaVir approach -- 7 In vivo electroporation -- 8 Electroporation-based Trigrid™ delivery system (TDS) for DNA vaccine administration -- 9 Prime Boost Regimens for Enhancing Immunity: Magnitude, Quality of Mucosal and Systemic Gene Vaccines -- 10 Intranodal genetic immunization -- 11 Immunotherapy of cancer with RNA vaccines -- 12 DNA and RNA vaccines for prophylactic and therapeutic treatment of type I allergy -- 13 Approved veterinary vaccines – paving the way to products for human use -- 14 Current status of regulations for DNA vaccines -- 15 State of the art production of antibiotic resistance-free plasmid DNA -- 16 Industrial Manufacturing of Plasmid-DNA Products for Gene Vaccination and Therapy.  .
Keywords: Vaccines; Immunology; Medical biochemistry; Vaccine; Immunology; Medical Biochemistry